Modeling of field emission from a sharp tip - Wong, William Chee Tat. (2010)
The interaction of the charged particles in a vacuum gap has essentially remained an area that is worth exploring in domains of accelerator physics, sheath physics, high current diodes, microwaves sources, and vacuum microelectronics including nano-electronics. Most of the theoretical developments focused on one dimensional (1D) classical models and they have extended to simple geometries or shapes.